Some Cars in Indonesia Have ‘Names’: A Linguistically Creative Use of Rebus - V. Luluk Prijambodo (Magister Scientiae, 2013)
The practice of name giving differs from language to language. A name can be given to a person, place or thing. Therefore, there are person names, place names, thing names. The fact, however, a person may be named after a place or even an animal name. The phenomenon discussed in this article shows another practice of name giving not to a person, place or thing, but to a car. That is a car is named after its owner. It is the implication beyond the name giving that this article intends to uncover.